Successive crystallization in indium selenide thin films for multi-level phase-change memory - Xu, Zhehao; Yuan, Yukang; Song, Sannian; Song, Zhitang; Liu, Ruirui; Zhai, Jiwei (Applied surface science, 2023)
[Display omitted] •Three resistance states with clear distinction are obtained in indium selenide phase-change thin films.•Amorphous indium selenide thin films crystallize at two different temperatures to form two crystalline phases.•Reversible switch between three resistance states as fast as 60 ns is implemented in In2Se3-based PCM cells.•Successive crystallization in indium selenide thin films is applicable to multi-level phase-change memory. Increasing the storage density of phase-change memory is a challenging subject towards the universal memory commercialization. Multi-level data storage can be implemented in phase-change memory cells by designing multiple stages of crystallization of phase-change materials, which is favorable to push forward the application of phase-change memory in storage-class memory and the emerging in-memory computing. Here, the structure and properties of In2Se3 phase-change thin films with multi-level phase transitions are investigated. The In2Se3 thin films changes resistance states twice upon heating with high crystallization temperature and good thermal stability. The amorphous In2Se3 thin films undergo partial crystallization of the Se phase followed by crystallization of the γ-In2Se3 phase, with successive stages of crystallization accounting for the three distinct levels of resistivity. The phase-change memory cell based on In2Se3 thin films shows a continuous switching process of high resistance state, intermediate resistance state and low resistance state with low drift coefficient in SET-RESET operations at a speed as fast as 60 ns, and the RESET power is as low as 311 pJ, indicating that the In2Se3 thin films have good performance of three-state storage property and can effectively improve the memory density.